2012
DOI: 10.1002/poc.2903
|View full text |Cite
|
Sign up to set email alerts
|

An ultrafast time‐resolved infrared and UV–vis spectroscopic and computational study of the photochemistry of acyl azides

Abstract: The photochemistry of pivaloyl, benzoyl, 4‐phenylbenzoyl, and 2‐anthroyl azides has been studied using femtosecond (fs) time‐resolved infrared (TRIR) and UV–vis spectroscopy and interpreted with the aid of computational chemistry. Density functional theory calculations revealed a significant difference in the nature of the lowest singlet excited state for these carbonyl azides. The lowest singlet excited states (S1) of p‐phenylbenzoyl and 2‐anthroyl azides are (π,π*) in nature, while the pivaloyl and benzoyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…Similar results were also found for other singlet nitrenes, and attributed to an intramolecular O→N interaction 15a. 19 Thus, nucleophilic attack of CO to the nitrene center is expected to occur from the opposite side of this supposed NO interaction, that is, the anti position with respect to the carbonyl oxygen.…”
Section: Experimental and Calculated Vibrational Frequencies [Cm−1] Osupporting
confidence: 69%
“…Similar results were also found for other singlet nitrenes, and attributed to an intramolecular O→N interaction 15a. 19 Thus, nucleophilic attack of CO to the nitrene center is expected to occur from the opposite side of this supposed NO interaction, that is, the anti position with respect to the carbonyl oxygen.…”
Section: Experimental and Calculated Vibrational Frequencies [Cm−1] Osupporting
confidence: 69%
“…Note that lower excited states of many organic azides, which correspond to the states populated after the nonadiabatic dynamics observed here, generally have lifetimes of a few hundred femtoseconds (62)(63)(64), while the lowest excited state has a lifetime of a few to several hundred picoseconds (65)(66)(67). The asymptotic (longtime) products formed from VUV excitation of methyl azide, which occurred after the short-timescale nonadiabatic dynamics discussed here, have been explored in detail by Wodtke and coworkers (68)(69)(70)(71), including minor pathways for ion-pair formation (71) and cyclic N 3 formation (70).…”
Section: Discussionmentioning
confidence: 66%
“…There were virtually no insertion or addition products observed as the analytical method of detection would have identified 1% yield of any of these products. 29 These experiments, along with a large number of other experimental, 31 theoretical, 32,33 and computational studies, 34,35 concluded that the thermal Curtius rearrangement is a concerted reaction as shown in Scheme 2. 31,32,36…”
Section: Mechanism Of the Curtius Rearrangementmentioning
confidence: 94%